Related factors based on non-targeted metabolomics methods in minor ischaemic stroke - Chen, Chen; Qiao, Xiaoyuan; Guo, Jianyong; Yang, Ting; Wang, Min; Ma, Yipeng; Zhao, Shuhe; Ding, Ling; Liu, Hong; Wang, Jintao (Frontiers in Endocrinology, 2022)
Objective: This study aimed to identify potential biomarkers associated with the occurrence of minor ischaemic stroke. Methods: Four hundred patients hospitalized with minor ischaemic stroke were enrolled in the department of neurological internal medicine in Taiyuan Central Hospital, and 210 healthy subjects examined at the Taiyuan Central Hospital Medical Center during the same period were selected. We collected information on the general demographic characteristics and fasting blood samples of the subjects. We then used untargeted metabolomic assay to measure blood glucose, blood lipids, homocysteine, and high-sensitivity C-reactive protein. Results: There were statistically significant differences between the mild ischemic stroke group and the healthy control group in smoking, hypertension, and physical activity (P < 0.05). Compared with the healthy group, the minor ischaemic stroke group showed increased lactate, pyruvate, trimetlylamine oxide levels, and lactic acid, pyruvic acid, and trimethylamine N-oxidation (TMAO) levels were statistically significant (P < 0.001). In the minor ischaemic stroke risk model, hypertension, physical activity, smoking, and elevated TMAO levels influenced the occurrence of minor storke. Conclusion: Increased levels of lactic acid, pyruvate, and TMAO may be related to the pathophysiological changes in the minor ischaemic stroke population. High blood pressure, a lack of physical activity, smoking, and increased TMAO level were the influencing factors for the occurrence of minor ischaemic stroke. The serum metabolite TMAO may be associated with MS occurrence